Environmental & architectural phenomenology. Vol. 16, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2005)
Vol. 16, No. 3, Fall 2005 (includes “citations received” and essays by Rachel McCann & Lin Wong).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals